Neferine alleviates chronic stress-induced depression by regulating monoamine neurotransmitter secretion and gut microbiota structure - Dong, Zaiquan; Xie, Qinglian; Xu, Feiyu; Shen, Xiaoling; Hao, Yanni; Li, Jin; Xu, Haizhen; Peng, Qiang; Kuang, Weihong (Frontiers in Pharmacology, 2022)
Neferine (Nef) might possess anti-depressive properties; however, its therapeutic effects are yet to be elucidated. Therefore, in this study, we aimed to explore the anti-depressant property of Nef using a mouse model of chronic stress-induced depression. Fifteen depression-prone mice were randomly selected and divided into three groups, namely, the model, Nef, and fluoxetine (Flu) groups. We observed that in tail suspension and forced swimming tests, the Nef and Flu treatments significantly decreased the immobility time of the depressed mice, and increased their sucrose preference indices. Moreover, both Nef and Flu treatments induced significant increases in the levels of anti-depressant neurotransmitters, including dopamine (DA), serotonin (5-HT), and norepinephrine (NE), and also reduced pathological damage to the hippocampus of the depressed mice. Incidentally, Illumina MiSeq sequencing analysis demonstrated that the relative abundance of Lactobacillus in the intestinal microbiota of depressed mice was restored after Nef/Flu treatment. Moreover, colonic Lactobacillus abundance was positively correlated with the levels of DA, 5-HT, and NE in the hippocampus of the mice. In conclusion, Nef improved monoamine neurotransmitter secretion and modulated the intestinal flora structure, particularly the abundance of Lactobacillus. Hence, it showed considerable anti-depressant potential, and might be a prospective anti-depressant therapeutic agent.